The Moderating Role of Seamless User Experience in Omnichannel Marketing and Customer Retention: A Technology Acceptance Model-Based Study in Emerging Markets - Akude, Derrick Nukunu; Agyapong , Gloria Kakrabah-Quarshie; Atuwo , Gladstone; Opoku , Nana Emmanuel; Glikpo, Obed Chris (Journal of Information Systems Engineering and Business Intelligence, 2025)
Background: In emerging markets, e-commerce firms increasingly adopt omnichannel marketing to enhance customer retention. A seamless user experience across digital and physical channels strengthens brand loyalty, yet implementation challenges remain significant due to infrastructural and connectivity constraints. Objective: This paper investigated the moderating role of seamless user experience on the relationship between omnichannel marketing and customer retention among E-commerce users in Ghana. Methods: The survey utilized a self-administered questionnaire approach, gathering a total of 384 completed responses for data analysis utilizing Smart PLS-SEM (version 4). Results: The study noted the occurrence of a positively significant relationship between cross-channel customer experience and customer retention. Secondly, there is a positively significant effect between channel service configuration and customer retention. However, the connection between channel integration quality and customer retention is insignificant. Moreover, the relationship between omnichannel personalization and customer retention is insignificant. Furthermore, seamless user experience has a positively significant moderation role in the connection between omni-channel personalization and customer retention. In addition, seamless user experience has a negatively significant moderation role in the relationship between channel integration quality and customer retention. However, seamless user experience has a positively insignificant moderation role in the relationship between cross-channel customer experience and customer retention. Also, seamless user experience has a positively insignificant moderation role in the relationship between channel service configuration and customer retention Conclusion: This investigation provides insights into the value of integrating seamless user experience to strengthen the relationship between omnichannel marketing as well as customer retention thereby highlighting their implications for theory, managers and business success. Keywords: Channel Integration Quality, Customer Retention, Seamless User Experience, Channel Service Integration, Cross-channel Customer Experience.